2011
DOI: 10.1007/s00423-011-0846-z
|View full text |Cite
|
Sign up to set email alerts
|

Body packers: a plea for conservative treatment

Abstract: BackgroundThe incidence of smuggling and transporting of illegal drugs by internal concealment, also known as body packing, is increasing in the Western world. The objective of this study was to determine the outcome of conservative and surgical approaches in body packers.Materials and methodsClinical data on body packers admitted to our hospital from January 2004 until December 2009 were collected. The protocol for body packers required surgery when packets were present in the stomach for >48 h. Outcomes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 19 publications
0
76
0
4
Order By: Relevance
“…The mortality and morbidity of these cases was once high because of the low quality of packaging and the primarily surgical treatment approach (5). Improved packaging material used by smugglers and a more conservative treatment approach have reduced the mortality and morbidity (5,9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality and morbidity of these cases was once high because of the low quality of packaging and the primarily surgical treatment approach (5). Improved packaging material used by smugglers and a more conservative treatment approach have reduced the mortality and morbidity (5,9).…”
Section: Discussionmentioning
confidence: 99%
“…2017; 19(2):e38964. 3 conservative management (1,5,11). The lack of an antidote makes cocaine intoxication dangerous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these first packets often tended to burst resulting in the loss of drugs and subsequent death of the body packer [12]." The 'lethal dose of cocaine ranges from 1 to 3 g' [12], so even one ruptured package could lead to acute cocaine toxicity and, if immediate action is not taken, death Figure 2 3-D-reconstruction of both packs in (E) with a clear depiction of the different densities" [13].As this method of drug trafficking has become more sophisticated and developed over time, new packaging has been produced. Now, "drug packets are machine produced and therefore uniform in size and weight.…”
mentioning
confidence: 99%
“…Now, "drug packets are machine produced and therefore uniform in size and weight. These newer packets consist of highly compressed drugs in several layers of latex [12]." Many published articles have found that the development of this new packaging has reduced fatalities and even the chance of packaging rupture during transit.…”
mentioning
confidence: 99%